From Komedie Stambul to Toneel: Theatre Arts Development in Batavia, 1891-1942 - Khairana Zata Nugroho; Dhanang Respati Puguh (IHiS (Indonesian Historical Studies), 2022)
Performing arts became a popular entertainment form among groups in the colonial era. People who enjoy performing arts were always craving for something new, and in turn, performing troupes were trying to create new innovations for their performances. In the late 19th century, a theatre group Komedie Stamboel was established in Surabaya. This group soon became popular because their uniqueness: the hybridity of their dramaturgies and stories which combined the West and East aspects. Their popularity resulted in a tour across Java, one of tour destinations was Batavia. When they were in Batavia, many of Komedie Stamboel’s performances were influenced by Indische culture and Indo people. By implementing the historical method, this article find the role of the Indo people and the influence of the Indische culture in Batavia’s development of  theatre arts. The increasing popularity of Komedie Stamboel resulted in imitators, both professional and amateur, with the majority of their performers consisted of Indo [hybrid] and Pribumi [local; indigenous]. Komedie Stamboel also developed into a theatrical genre known as komedie stambul. In the 20th century, a  theatre form known as Toneel Melajoe emerged as a continuity of the Komedie Stambul with new additions. Other theatrical genre known as Indische Toneel, a colonial  theatre created by playwrights of Dutch totok and Indo descent that often held in theatres  in Batavia. They had komedie stambul influences and Indische culture references on them.